The Triumph of Democracy and the Eclipse of the West - Harrison, Ewan. author. aut Link
XVIII, 265 p.
Keywords: This book explores the paradox of the worldwide spread of democracy and capitalism in an era of Western decline. The rest is overtaking the West as Samuel Huntington predicted, but because it is adopting Western institutions. The emerging global order offers unprecedented opportunities for the expansion of peace, prosperity, and freedom. Yet this is not the 'end of history', but the beginning of a post-Western future for the democratic project. The major conflicts of the future will occur between the established democracies of the West and emerging democracies in the developing world as they seek the benefits and recognition associated with membership of the democratic community. This 'clash of democratizations' will define world politics.